Circulating complement proteins in patients with sepsis or systemic inflammatory response syndrome. - Stöve, S (1996)
The systemic inflammatory response of the body to invading microorganisms, termed sepsis, leads to profound activation of the complement system. Pathophysiological concepts suggest that complement activation occurs very early in this syndrome. Thus, we discuss whether the determination of concentrations of the complement components C3a, C5a, and C3 in plasma as well as of the C3a/C3 ratio might be helpful to diagnose sepsis early. For this purpose, 33 patients from an intensive care unit were monitored for 10 days. In comparison with healthy donors, C3a levels and the C3a/C3 ratio of intensive-care-unit patients were significantly elevated (P < 0.0001) on admission. In contrast, C3 levels were significantly reduced (P < 0.0001) but increased during the study. C5a levels in the plasma of healthy donors and patients were identical. Twenty-two of 33 patients fulfilled microbiological and clinical criteria of sepsis. Eleven patients had signs of systemic inflammatory response syndrome but no microbiological evidence of sepsis. The groups could be differentiated from each other by their C3a levels or their C3a/C3 ratios during the first 24 h after the clinical onset of sepsis (P < 0.05). Septic patients in shock had higher C3a levels than normotensive septic patients, although the differences were not significant. Nonsurvivors had significantly higher C3a levels on admission than survivors (P = 0.0185). No differences were found between septic patients who developed adult respiratory distress syndrome and those who did not. Thus, determination of C3a concentrations in plasma may prove useful (i) to diagnose sepsis early, (ii) to differentiate between patients with sepsis and those with systemic inflammatory response syndrome, and (iii) to assess prognosis.